The vision for public health dietitians' skill improvement over the next 10 years in Japan: A qualitative study - Tatsuya Koyama; Yusuke Arai; Ayaka Iida; Sumie Isobe; Okamoto Rie; Izumi Shibuya; Kazumi Tanaka; Ayumi Morooka; Katsushi Yoshita (Elsevier, 2023)
Objectives: To obtain the basis for developing a new human resource development program. We examined the association between their position type and their vision for skill improvement in the profession in the next 10 years. Study design: This was a qualitative study. Methods: In 2021, we conducted an exhaustive survey of Japanese public health dietitians working in Japanese local governments. Using qualitative content analysis, we analyzed the participants' descriptions of how the profession could improve their skills over the next 10 years. Results: Regardless of the participants' organization of employment or their target position type, seven common categories were extracted; [goals], [health promotion activities], [organizational activities], [evaluation from others], [cooperation], [skills to be acquired], and [means for improving skills]. Depending on the organization type, 35-40 subcategories were extracted from those who wanted to be staff, 35-38 subcategories from those who wanted to be supervisors, and 20-37 subcategories from those who wanted to be managers. Different subcategories were extracted to describe the difference between specialists and generalists in [goals]. Participants described challenges with [evaluation from others] and [collaboration], regardless of the target position type or [goals]. Conclusion: The vision for Japanese public health dietitians' skill improvement to achieve in the next 10 years describes challenges with business evaluation and collaborative work. However, participants differed across what skills they wanted to improve based on the direction of their careers. To offer public health dietitians learning content that connects with their desired direction, a new human resource development program needs to be considered.